Partisipasi Kontak Tani Dalam Perencanaan Program Penyuluhan Pertanian di Kecamatan Konda Kabupaten Konawe Selatan - Dzoelkarman, Dzoelkarman; Salam, Idrus; Hamzah, Awaluddin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This research was conducted in Konda Subdistrict, South Konawe Regency from July to August 2017. The purpose of this study was to determine the level of farmer participation in planning agricultural extension programs in Konda Subdistrict, South Konawe District. The population of agricultural contacts is 118 people and the number of contact samples of selected farmers is 32 people plus 1 informant namely Field Extension Officer (PPL), sampling technique is done randomly using the method (Simple Random Sampling) of the total population 118 and Number of respondents taken as a sample of 32 people. Data analysis techniques used are quantitative and quantitative by tabulating and presented. Based on the description of the discussion from the results of the research conducted, it can be concluded that the level of farmer contact participation in planning agricultural extension programs in Konda Subdistrict is generally classified into the medium category (53.12%), in the low category (37.5%), and in the category high as much (9.37%) Forms of farmer contact participation in giving and receiving information Generally classified as high (50%), in the moderate category as much (34.37%), and in the low category as much (15.62%). Participation in giving responses and suggestions is generally classified as low (50%), in the moderate category as much (34.37%), and in the high category as much (15.62%). While participation in planning extension programs is generally classified as moderate (56.25%), in the low category as much (25%), and in the high category as much (18.75%).